Debt, Profitability, and Firm Size and Their Effects on Income Smoothing - Setiadi Alim Lim (CONTABILITA : Journal of Accounting and Finance, 2026)
This research is classified as quantitative research to test the hypothesis, and is intended to examine whether there is an influence of the independent variables, namely debt, profitability, and company size on the dependent variable, namely income smoothing practices. The debt variable is proxied by the debt equity ratio, profitability is proxied by return on assets, and company size is proxied by total assets. Meanwhile, income smoothing practices are dummy variables that indicate the presence or absence of income smoothing practices based on the Eckel index. This study took a population of all companies on the Indonesia Stock Exchange (IDX) listed in the infrastructure sector, wired telecommunication service sub-industry, and obtained 21 companies. The sampling method used non-probability purposive sampling and obtained 15 companies as samples. The data used is a type of secondary data, in the form of company financial report data for the period 2015-2024. To test the effect of debt, profitability, and company size on income smoothing practices, logistic regression was used. The results of the logistic regression indicate that debt, profitability, and company size simultaneously do not affect income smoothing practices. Meanwhile, partial testing shows that of the three independent variables used, only one independent variable influences income smoothing practices, while the other two independent variables do not. The independent variable that influences income smoothing practices is company size, and the independent variables that do not influence income smoothing practices are debt and profitability.